Mechanism of Action of Tumorigenesis of Anticancer Molecules of Palm Oil Tocotrienols (Elaeis Guieensis Jacq.): A Systematic Review - Humairah Medina Liza Lubis; Emni Purwoningsih; Annissa Ambaravista Nasution; Qatrunnada Medina Salim (Green Publisher Indonesia, 2022)
Palm oil contains vitamin E which comprises two structurally similar compounds namely tocopherols and tocotrienols. For many years tocopherols considered the best therapy in curing disease, but in recent research advances, tocotrienol has been widely used as a powerful therapy in several diseases, including cancer. We prepared this article to review and analyze the role of tocotrienols from palm oil as anticancer molecules and their mechanism of action in the process of tumorigenesis based on the literature from PubMed, Scopus, Science Direct, and ProQuest databases published from 2011 to 2020, and according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Nineteen English articles and abstracts according to the inclusion criteria, systematically reviewed and compiled. The results showed that tocotrienol acts on intracellular and extracellular targets involved in cell signaling pathways and suppresses the growth of various malignancies, including breast, lung, prostate, ovarian, liver, brain, colon, pancreatic, and myeloma cancers. This literature review shows that the molecular mechanism of action of tocotrienols has several advantages, namely a positive effect on cell proliferation, apoptosis, angiogenesis, metastasis, and inflammation, which when working together can function as effective agents in cancer therapy. The tocotrienol-mediated therapeutic action mechanism could help clinicians to design new strategies for cancer treatment.